(untitled) (Global Journal of Management and Business Research, 2019)
The objective of this study is to measure the Microfinance institutions (MFI) efficiency levelsin Cameroon. We then apply the non-parametric method Data Envelopment Analysis (DEA) on a sample of 47 Microfinance institutions (MFI) belonging to the MC2 network. The DEA model permitted us to appraise the MFI efficiency levels. The DEA model therefore shows that the Cameroon MC2 network MFI are technically efficient taking in consideration the two types of return on scale. This study permit us to know the efficiency levels of MFI living in the same group.